Sugarcane Pulp Take-Out Containers Produce More Microparticles in Acidic Foods - Yi Hu; Chun-Ru Mo; Zhi-Wei Wang; Wen-Wen Yu; Chang-Ying Hu (Foods, 2023)
In the current study, the production of microparticles released from fifteen commercial sugarcane pulp (SCP) take-out containers into different food simulants under different conditions was investigated, where deionized water (DI water), 4% acetic acid (4% HAc), and 95% ethanol (95% EtOH) were used to simulate aqueous, acidic, and fatty foods, respectively. Results showed that compared with DI water and 95% EtOH, 4% HAc caused the degradation of sugarcane fibers, thereby releasing the highest number of microparticles. The overall migration values of the sugarcane pulp take-out containers in 4% HAc were above the prescribed limit of 10 mg/dm2. Furthermore, it was estimated that consumers may intake 36,400–231,700 microparticles in a take-out container at one time, of which the proportion of particles with a particle size between 10 and 500 μm was the highest, ranging from 26,470 to 216,060 items. Moreover, the Al and Fe are the main metals in these take-out containers, ranging between 35.16 and 1244.04 and 44.71 and 398.52 mg/kg, respectively, followed by Pb, Ti, and Sr. This study provides important information that the safety of both the production of microparticles and the metallic elements should be considered for SCP take-out containers when in contact with food.